Application of Criminal Sanctions Against Perpetrators of Criminal Acts of Persecution That Cause Minor Injuries (Study of Decision Number: 3/Pid.C/2021/PN Gdt) - Lukmanul Hakim; Okta Ainita; Muhamat Ilza Amanda (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to examine the application of loan sanctions against perpetrators of criminal acts of persecution that cause minor injuries in the criminal justice system. Mistreatment resulting in minor injuries is a frequent criminal act and has a significant impact on the victim. The research method used in this study is a normative research method using a legislative approach and a case approach and will be analyzed using content analysis. which is related to the application of loan sanctions in cases of mistreatment with minor injuries. The problems that will be discussed in this study are related to the application of criminal sanctions against perpetrators of criminal acts of persecution that cause minor injuries.